Guardians of the galaxy : Can't fight this seedling - Caramagna, Joe (Guardians of the Galaxy, 2018)
"On a mission to find the next Pandorian Crystal, the Guardians encounter a race of aliens that are under attack by rock-like Rexians and help fight them off, but Groot becomes infected with the same fungus that possesses the Rexians"--Publisher.